Exposure to acute restraint stress reinstates nicotine-induced place preference in rats - Leao, Rodrigo M. [UNESP]; Cruz, Fabio C. [UNESP]; Planeta, Cleopatra da Silva [UNESP] (Lippincott Williams & Wilkins, 2009)
Tobacco addiction is associated with high rates of relapse to drug use even after prolonged periods of abstinence. Relapse can occur upon reexposure to the drug of abuse, exposure to stress or to stimuli associated with drug consumption. The reinstatement of conditioning place preference (CPP) provides a simple and easy approach to investigate the mechanisms for drug relapse. We evaluated whether exposure to restraint stress could reinstate nicotine-induced CPP 1 or 15 days after its extinction. Nicotine produced place preference to the compartment paired with its injections during conditioning (0.16 mg/kg, subcutaneous; four drug sessions). Once established, nicotine CPP was extinguished by alternate exposure to each compartment after a saline injection (four exposures to each compartment). After this extinction phase, the reinstatement of place conditioning was investigated. For this purpose, rats were exposed to 30-min restraint stress 1 or 15 days after the extinction test, then immediately tested for reinstatement of CPP. Our results show that exposure to restraint stress reinstated CPP 1 and 15 days after extinction. Our study indicates for the first time that the vulnerability to stress-induced reinstatement of nicotine CPP is long-lasting, corroborating clinical studies showing that stress is positively associated with relapse to tobacco use even after along period of nicotine withdrawal. Behavioural Pharmacology 20:109-113 (C) 2009 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: conditioned place preference; nicotine; rat; reinstatement; stress